Optimized Model Inputs Selections for Enhancing River Streamflow Forecasting Accuracy Using Different Artificial Intelligence Techniques - Tofiq Y.M.; Latif S.D.; Ahmed A.N.; Kumar P.; El-Shafie A. (Springer Science and Business Media B.V., 2023)
Dams; Decision trees; Forecasting; Forestry; Information management; Irrigation; Reservoir management; Reservoirs (water); Stream flow; Support vector machines; Water management; Water supply; Aswan high dam; Boosted tree regression; High dams; Inflow predictions; Intelligence models; Random forest modeling; Random forests; Streamflow prediction; Support vectors machine; Tree regression; Neural networks; accuracy assessment; algorithm; artificial intelligence; artificial neural network; forecasting method; numerical model; regression analysis; river flow; streamflow; support vector machine; Aswan Dam; Aswan [Egypt]; Egypt